Parental Collaboration as a Strategic Driver of Quality Management and Institutional Resilience in Islamic Boarding Schools - Nurur Rifqotul Maulidah; Abdullah (Al-Qalam Institue, 2026)
This study examines the impact of parental collaboration based on criteria derived from quality management and institutional resilience frameworks in Islamic boarding school–based junior high schools. The research aims to analyze how parental collaboration contributes to strengthening quality management practices and enhancing institutional resilience in responding to internal and external challenges. Employing a qualitative research approach, data were collected through in-depth interviews, observations, and document analysis, and analyzed using quality management perspectives developed by Deming and Juran. The findings reveal that parental collaboration plays a strategic and potential role in reinforcing the foundations of quality management and supporting institutional recovery and improvement following periods of resilience. Effective partnerships between parents and educational institutions are shown to enhance service quality, strengthen institutional components, and build a positive organizational image through both internal and external social relationships. Furthermore, in the context of boarding school–based institutions, intensive institutional objectives foster stronger branding ties between parents and schools, contributing to sustainable quality improvement and long-term institutional resilience.